“Many People Do Not Consider Us Human” Violence Against Commercial Sex Workers in Gondar City: A Phenomenological Study - Habitu Birhan Eshetu; Amare Zewdie; Eshetu Girma; Ayenew Kassie; Asmamaw Adugna; Adane Nigusie; Simegnew Handebo (SAGE Open)
Sex workers are a marginalized group that often faces a heightened risk of experiencing violence, however little is known from the perspectives of sex workers in Ethiopia. Therefore, this study was conducted to explore the violence experienced by commercial sex workers in Gondar City, Northwest Ethiopia. An exploratory qualitative study using a phenomenology approach was conducted from October to November 2020 in Gondar City. A snowball purposive sampling method was used to recruit 12 commercial sex workers. A face-to-face in-depth interview was conducted. The collected data were analyzed using the thematic analysis approach. Open code version 3.1 software was used for data analysis. Commercial sex workers experienced substantial violence during their work. Sexual, physical, psychological, economic, and structural violence, perpetrators, and mechanisms to deal with the violence were the main themes that emerged from the analysis. Sexual violence mainly occurred from disagreement on sex without a condom, sexual position, a request for oral and anal sex, and extended duration of intercourse were a source of all other types of violence. Commercial sex workers experienced considerable sexual, physical, emotional, and economic violence. It is recommended that efforts should be made to raise awareness about women’s rights and their need for legal and healthcare services. Additionally, it emphasizes the importance of providing life skills to empower women, such as financial, domestic, survival, goal-setting, communication, relationship-building, boundary-setting, and problem-solving skills. These skills are mentioned as a means to help prevent or reduce the violence experienced by commercial sex workers.